2021
DOI: 10.1186/s12915-021-01183-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of phosphatidylserine/PI(4)P exchangers with diverse lipid species and membrane contexts reveal unanticipated rules on lipid transfer

Abstract: Background Lipid species are accurately distributed in the eukaryotic cell so that organelle and plasma membranes have an adequate lipid composition to support numerous cellular functions. In the plasma membrane, a precise regulation of the level of lipids such as phosphatidylserine, PI(4)P, and PI(4,5)P2, is critical for maintaining the signaling competence of the cell. Several lipid transfer proteins of the ORP/Osh family contribute to this fine-tuning by delivering PS, synthesized in the end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 74 publications
0
24
1
Order By: Relevance
“…Otherwise, a lipid with an excessive binding affinity for the LTP would be trapped in the binding cavity and block the exchange reaction. Consistent with this view, the LTP-lipid binding affinity appears to be tuned to a similar level for efficient exchange of the cognate lipids (Ikhlef et al ., 2021). Therefore, based on the energetics of lipid extraction and solubilization, we hypothesize that shuttle LTPs are generally lipid exchangers.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Otherwise, a lipid with an excessive binding affinity for the LTP would be trapped in the binding cavity and block the exchange reaction. Consistent with this view, the LTP-lipid binding affinity appears to be tuned to a similar level for efficient exchange of the cognate lipids (Ikhlef et al ., 2021). Therefore, based on the energetics of lipid extraction and solubilization, we hypothesize that shuttle LTPs are generally lipid exchangers.…”
Section: Introductionmentioning
confidence: 75%
“…Our model of lipid exchange differs from the previous model developed by Drin and coworkers (von Filseck et al ., 2015b; Ikhlef et al ., 2021), in which several intermediate states of Osh4p-mediated lipid transfer are included, for example, the states in which Osh4p is bound to the membrane but not loaded with any lipid. Consequently, the model contains six coupled reactions with more than 10 rate constants, which make it difficult to derive an analytical solution for the lipid transfer rate and fit the model to experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the conversion of PS to PI4P depends on lipid transfer proteins (LTPs), and PS species affect LTP activity. Experimental results indicated that one double bond in either PS acyl chain was enough to markedly change the rate of PS conversion into PI4P, 48 showing that PS species distribution can modify insulin signal transduction. In addition, via its C1q domain, adiponectin binds to PS and sphingolipids, which may be related to dead cell clearance.…”
Section: Transductionmentioning
confidence: 99%